GAME EDUKASI TRIGONOMETRI BERBASIS WEB UNTUK MEDIA PEMBELAJARAN - Masum, Masum; Romdoni, Mochamad Yusuf; Hermanto, Rendi (Teknik Informatika Fakultas Ilmu Komputer, 2018)
Mathematics is a subject that is considered the most difficult by most students, especially students who are at the high school level or equivalent. At this level mathematics subjects increasingly difficult because of the material being studied more and more difficult with many sample questions that confuse. More specifically on the material of Trigonometry. In this material the student demanded to be able learn of Trigonometry with the help of trigonometric tables. The problem in the table there are numbers that are not easy to be memorized in a short time. With teaching and learning activities that are still classic by relying on the teacher to explain the material in front of the class, most students feel bored with the activity. So it needed the learning media that may facilitate students in memorizing content trigonometric tables. One feasible alternatives is using games as learning media. The purpose of this game is to deliver the materials of trigonometry in the form of a game, so that as if the players are in the game and they unconsciously learn content trigonometric tables. Besides this game will provide an alternative model of active learning, initiative and also fun.